IMPLEMENTASI PENDIDIKAN AGAMA DAN KE AGAMAAN PASCA KONFLIK DI DAERAH MAMBI SULAWESI BARAT - Rosdiana Rosdiana (Balai Penelitian dan Pengembangan Agama Makassar, 2008)
This research aims to describe the implication of social conflict to educationof religion (formal and informal) implementation. This was conductedat Mambi, West Sulawesi. Data was collected by depth interviewand observation.This research indicates that social conflict atAralle, Tabulahan, Mambiduring 2002-2005 had give impact the some education of religion implementation,such as (a) system of school administration was disfunction,(b) number of teachers and students was decrease. Most of them wentout to another place. Nevertheless, .this conflict didn't influence to thelearning process of religion education and religion activity.